(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this article, language competence in lower grades is developed through conscious assimilation of language rules and their correct application in practice. The main task of supervision is aimed at systematic assessment of students’ knowledge and skills in each section of language rules and their improvement.